Risk factors for moderate disturbance of consciousness in patients with unilateral chronic subdural hematoma - Adrian Liebert; Thomas Eibl; Thomas Bertsch; Hans-Herbert Steiner; Karl-Michael Schebesch; Leonard Ritter (Interdisciplinary Neurosurgery)
Objective: Chronic subdural hematoma (CSDH) patients usually present with mild symptoms; however, a subset of patients presents with disturbance of consciousness (DOC). We analyzed clinical and radiographic factors, which could influence the level of consciousness in CSDH patients before surgery. Methods: We retrospectively analyzed consecutive unilateral CSDH patients, who were surgically treated in our department from 2018 to 2023. We compared a group of patients with moderate DOC (group 1), defined as a Glasgow Coma Scale (GCS) 9–13, with a control group of awake but symptomatic patients (GCS > 13, group 2). Clinical and radiographic parameters were analyzed in bivariate and multivariate analyses. Results: 41 (12.9 %) patients presented with GCS 9–13 and 276 patients with GCS > 13. In bivariate analysis, radiographic parameters, like greater mean midline shift (p < 0.001), homogenous hypodense type (p = 0.017), additional temporal (p < 0.001) and occipital (p < 0.001) location, “acute-to-chronic” (p = 0.002) and “acute-on-chronic” (p = 0.049) forms were more frequent in group 1. The trabecular hematoma subtype was less common in group 1 (p = 0.002). INR (p = 0.004) and CRP values (p = 0.003) in the preoperative blood sample were significantly higher in group 1. History of ischemic stroke and intake of statins were more common in group 1 (p = 0.033, p = 0.04; resp.). In the multivariate analysis, midline shift (p = 0.033), occipital location (p = 0.005) and history of ischemic stroke (p = 0.046) remained significant. Conclusion: We could identify factors which contribute to DOC in CSDH patients. Among those are greater midline shift, occipital location and history of ischemic stroke as independent risk factors.